2001
DOI: 10.2170/jjphysiol.51.555
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pCO2 on the CSF Turnover Rate in Rats Monitored by Gd-DTPA Enhanced T1-Weighted Magnetic Resonance Imaging.

Abstract: Hypercapnia produces a vasodilatation of the cerebral vasculature with an increase in cerebral blood flow and hypocapnia causes vasoconstriction with a decrease in cerebral blood flow. The cerebrospinal fluid (CSF) pressure was increased by hypercapnia and decreased by hypocapnia [1]. This suggested that the formation of CSF might be altered by carbon dioxide. However, we have seen conflicting results in regard to the influence of hypercapnia and hypocapnia on CSF formation [2][3][4][5][6]. To confirm the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
11
1
Order By: Relevance
“…On the other hand, in the absence of perfusion, the long-term viability of these preparations was drastically impaired. Interestingly, media turnover rates (∼0.15%/min) were one to two orders of magnitudes lower than cerebrospinal fluid (CSF) turnover rates in the intact rat brain (1% to 16%/min; [55]), indicating that perfusion rates were not excessively high.…”
Section: Resultsmentioning
confidence: 97%
“…On the other hand, in the absence of perfusion, the long-term viability of these preparations was drastically impaired. Interestingly, media turnover rates (∼0.15%/min) were one to two orders of magnitudes lower than cerebrospinal fluid (CSF) turnover rates in the intact rat brain (1% to 16%/min; [55]), indicating that perfusion rates were not excessively high.…”
Section: Resultsmentioning
confidence: 97%
“…Real-time neuroimaging studies in the rat have revealed that material injected into the lateral ventricle appears almost simultaneously in the upper part of the third ventricle, which communicates with the lateral ventricles via the foramen of Monro, and peaks in the posterior third ventricle within 2 min of injection at a signal intensity 75-90% of that observed in the lateral ventricle (Bui et al 1999;Takamata et al 2001). Consistent with these observations, radiolabeled leptin has been shown to penetrate more than 200 μm into periventricular structures of the third ventricle within 2 min of infusion into the lateral ventricle (Maness et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…At the pretreatment interval used in the present study (30 min), leptin infused into the lateral ventricle would have penetrated more than 600 μm into structures that surround the third ventricle by the onset of testing (Maness et al 1998), thereby enveloping the arcuate nucleus, a putative site of action. Thus, while third versus lateral ventricle of administration might account for differences in potency, it is unlikely to result in different modes of action because of the substantial, rapid flow of CSF between the lateral and third ventricles (Maness et al 1998;Bui et al 1999;Takamata et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In most mammals, it takes about 200 min for the secretion of an amount of CSF replacing the total volume of CSF in the ventricles (Cserr 1971). For rats, longitudinal relaxation timeweighted magnetic resonance imaging after intraventricular injection of the T 1 -relaxation reagent Gd-DTPA showed that the whole ventricular space is not a single compartment (Takamata et al 2001). Probably, the flow of CSF through the ventricular system involves both laminar and turbulent flow, the proportions of which differ from region to region.…”
Section: Discussionmentioning
confidence: 99%